Urban water supply in Tanzania: the case of Hai Water Project in Kilimanjaro Region and Dar es Salaam City - Reweta, Wande S. J., author; Sampath, R. K., advisor; Davies, Stephen P., committee member; Terutomo, Ozawa, committee member; Dalsted, Norman L., committee member (Colorado State University. Libraries, 2001)
Urban water supply and sanitation services have captured the world attention for several decades. While experts around the world agree that an adequate provision of this resource is crucial for the well being of the people, the demand for it, particularly in developing countries has always surpassed its supply. Where water supply projects has been constructed, issues of equity, efficiency, cost recovery, sustainability as well as whether or not beneficiaries are willing and able to pay for service improvements have been raised. In this study, sustainability is addressed by evaluating equity in water delivery in terms of the distribution of public taps among different villages and townships in the Hai Water Project Area - Kilimanjaro Region, comparing inter-temporal and intra-temporal billing collection efficiency between households and public tap consumption in villages and townships as well as comparing revenue from bills collected to the operations and maintenance costs of the project. The results from this study show that public taps are unevenly distributed among beneficiaries. Performance in bills collection is better for the public taps than for household connections, and overall, townships' performance is better than that of villages. Water supply performance in Tanzania is assessed by evaluating equity and efficiency aspects of urban water supplies in the city of Dar es Salaam in terms of the amount of water supplied to different districts and Dar es Salaam Water and Sewerage Authority (DAWASA) branches. The study concludes that the city is faced with an acute water supply problem, water is unevenly distributed at all levels and that inequality between and within districts is likely to increase over time. The study also estimates the Willingness to Pay for improved water supply (quantity) in the city of Dar es Salaam as well as the premium that residents are willing to pay for quality improvement. Results show that households in the city are willing to pay on average Tsh. 2,685 over and above their current monthly water bill for improvement in water supply (quantity) and Tsh. 537 over and above the amount for supply improvement as quality premium. Lastly, the study estimated the benefits of increased potable water supply for the city of Dar es Salaam. A Marshallian partial analysis is used to estimate consumer and producer surpluses arising from such an improvement. Results show that the net benefits to both consumers and producers is positive.
Keywords: projects; urban areas; water supply; studies; urban planning; sustainability; households